Perspectives of High School students in DIY province on Esport - Kurniawan, Faidillah; Sumaryanto, Sumaryanto; Hidayatullah, Muhammad Furqon; Kristiyanto, Agus; Riyadi, Slamet (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2024)
This study aims to explore the perspectives of high school students in DIY towards e-sports. The research found that the majority of students had a positive view, recognizing it as a legitimate form of competition and a thriving industry. However, some students expressed concern about the negative effects of excessive gaming, such as addiction and social isolation. This study uses exploratory research methods. Exploratory research explores new knowledge to try to discover existing or potential problems. The sample used was high school students in DIY, totaling 276 people with 188 male students and 88 female students. The research instrument used was a questionnaire distributed in the form of a Google form. The results of this study showed that 68.1% were male and 31.9% female. Of the total number of students who actively played e-sports 48.9% and 51.1% did not actively play. esport can improve English proficiency with 68.1% disagreeing at 6.4%. The students also like watching matches through the livestream platform 51.1% and disagree 17%. Esports can also be said to be a promising field of work by agreeing at 57.4%, on the otherhand disagreeing at 4.3%. Students also like to play e-sports with an agree rate of 61.7%, although those who disagree are 6.4%. e-sports can be categorized as sports with the number agreeing at 61.7%, and those who disagree are 2.1%. The students also agreed with e-sports they got a lot of acquaintances with a rate of 59.6% and disagreed with 6.4%.